颈后路单开门椎管扩大成形术全钛板与交替钛板、缝线固定治疗颈椎病的对比研究 (Beijing Da Xue Xue Bao Yi Xue Ban, 2019)
OBJECTIVE: To retrospectively compare the effect of alternate levels miniplate and anchor fixation with the effect of all levels miniplate fixation in expansive open-door cervical laminoplasty (EOLP). METHODS: Patients with cervical spondylosis underwent EOLP between July 2015 and June 2016 were included in the study. There were 33 patients in the alternate group (alternate levels miniplate and anchor fixation group) and 34 patients in the miniplate group (all levels miniplate fixation group). Neurological function was evaluated with the Japanese Orthopedic Association (JOA) score and degree of pain was assessed with the visual analogue scale (VAS) score. Basic clinical and surgical data, complication rates and medical costs of the two groups were compared. In addition, radiological examinations were performed pre- and post-operatively and at the final follow-up. Relative imaging data such as anteroposterior diameter (APD), cervical curvature index (CCI) and open angle were collected and compared. RESULTS: (1) The mean follow-up time was 18.6 months in the alternate group and 18.9 months in the miniplate group. There were no significant differences in operation time, intraoperative blood loss, perioperative complication rates, post-operative hospital stays, VAS scores and neurological recovery rates preoperatively and at the final follow-up between the two groups. (2) Additionally, no obvious differences were observed about CCIs and APDs at the three follow-up time points between the two groups. Post-operative open angles at C4 and C6 in the alternate group were significantly smaller than those in the miniplate group. However, there were no significant differences in C3, C5 and C7 open angles between the two groups post-operatively. Notably, no significant differences were detected about the open angles at all levels between the two groups at the final follow-up. (3) When comparing radiologic data at different time points in each group, CCIs and open angles at each level had no significant differences, but APDs after surgery and at the final follow-up were significantly larger than pre-operative APDs. (4) Total costs in the alternate group were significantly lower than those in the miniplate group. CONCLUSION: The two surgical methods showed almost the same neurological recovery rates and complication rates. However, use of alternate levels miniplate and anchor fixation in EOLP can reduce medical expenses.